Implementasi Metode Drill Dalam Meningkatkan Hafalan Kosakata Bahasa Arab Di Madrasah Aliyah Al Amiriyyah Blokagung Banyuwangi - Nur Maya Badriyatul Jamroh; Khoiratun Nisa (Institut Agama Islam Darusssalam Blokagung, 2021)
Drill method is one of the methods used in learning. The Drill method is an exercise with practice that is carried out repeatedly continuously to gain practical skills and dexterity about the knowledge learned. This study aims to determine the implementation of the drill method in improving the memorization of Arabic vocabulary and its advantages and disadvantages at Madrasah Aliyah Al Amiriyyah Blokagung Banyuwangi. This research is a descriptive qualitative research. by using data collection techniques by observation, interviews and documentation and data analysis with interactive models, namely data collection, data reduction, data presentation and drawing conclusions, and using data validity in the form of triangulation. The results showed that the implementation of using the drill method for memorizing Arabic vocabulary had increased. This can be seen by the increase in Arabic vocabulary when learning Arabic subjects. However, there are also advantages and disadvantages in using the drill method. Among the advantages of using the drill method, students are easy to memorize vocabulary, easy to remember and foster student enthusiasm. Meanwhile, the disadvantages are that the students are depressed because of their weakness in memorizing and the students feel bored because of the repetition of vocabulary.